TECHNIQUE APPROACHES IN TEACHING FOREIGN LANGUAGE TO STUDENTS OF ECONOMICS - Mariia O. Kuts (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article reveals the problem of increasing the efficiency of teaching foreign languages to students of non-linguistic specialties by means of introducing a system of pedagogical teaching technologies into the educational process. It has been determined that pedagogical technologies of teaching are such pedagogical technologies, which are based on modern positions of professional development of a person and aimed at achieving educational goals. In the process of learning foreign languages, they are a way of a phased system of organization of the communicative interaction between a teacher and a student in the conditions of operative feedback between them through the use of specific methods, forms and means of learning. It has been found that the leading class of pedagogical technologies for teaching foreign languages is a communicatively oriented technique – a project technique and an appropriate system of its successive and phased implementation, in which learning emerges as a model of real-world foreign communication. The article provides a classification of pedagogical techniques for teaching foreign languages to students of the economic area of expertise, which can contribute to their more systematic use to improve the efficiency of the educational process in higher education institutions. Among the subspecies of communicative oriented techniques of teaching foreign languages to students of economic specialties the following subcategories have been identified: subjects of educational process management – techniques of teaching, learning, partnership interaction and instrumental techniques; the place in the organization of the educational process – the technique of in-class, out-of-class and independent activities; according to the methodological approach – technique-modernization and technique-transformation and in the terms of implementation – meta-techniques, branch macro techniques, modular-local and micro techniques. The author sees the directions for further research in the development of tools for the implementation of the above techniques in accordance with the characteristics of the professional training of students of economic area of expertise.